RANCANG BANGUN DAN IMPLEMENTASI WEB SERVICE PADA SISTEM INFORMASI AKADEMIK BERBASIS MOBILE STUDI KASUS DI UNWAHA - Kurnia Andi Nugroho; Munawarah Munawaroh; Tholib Hariono (SAINTEKBU, 2020)
One of the implementations of information and communication technology is the information system. University of KH. A. Wahab Hasbullah which already has an Academic Information System (SIA) based on a web platform that can serve the needs of managers, lecturers and students related to academic activities. Students get academic information including study plan card information, study result cards, and other academic information starting with the input of the SIA url on a web browser which is done manually. With this flow, there are still some students who are late to get information about academics. The purpose of this study is to identify the application and implementation of a web service in handling data transmission from the client to the server. The mobile-based academic information system application is built using framework7 as a front-end and also acts as a client consumer, the data storage structure in the application uses MySql services as a database to store data and acts as a server, in every relationship between the client to the server is handled by the REST web service which has http request and response protocols. In cross-platform creation, the system has been integrated with a web-view hybrid modeling to support cross-platform, Apache Cordova framework makes it easy to build applications into a mobile form. The final result of this research is the creation of a mobile SIA application along with the implementation of a web service to make it easier for students to obtain information on KRS, KHS, and Heregistration Information at University of KH. A. Wahab Hasbullah. Keywords: Web Service, Academic Information Systems, Mobile, Framework7, Apache Cordova.